Effects of Deer Settling Stimulus and Deer Density on Regeneration in a Harvested Southern New England Forest - Kevin J. Barrett; Oswald J. Schmitz (International Journal of Forestry Research)
Elevated deer densities have led to reports of forest regeneration failure and ecological damage. However, there is growing evidence that the biophysical conditions of a forest that make it attractive to deer may be a contributing factor in determining browsing levels. Thus, an understanding of settling stimulus—how attractive an area is to deer in terms of food-independent habitat requirements—is potentially important to manage deer browsing impacts. We tested the settling stimulus hypothesis by evaluating the degree to which thermal settling stimulus and deer density are related to spatial variation in browsing intensity across different forest harvesting strategies over the course of a year. We determined if deer were impacting plant communities and if they resulted in changes in plant cover. We quantified the thermal environment around each harvest and tested to see if it influenced deer density and browsing impact. We found that deer had an impact on the landscape but did not alter plant cover or diminish forest regeneration capacity. Deer density and browse impact had a relationship with thermal settling stimulus for summer and fall months, and deer density had a relationship with browse impact in the winter on woody plants. We conclude that thermal settling stimulus is an important predictor for deer density and browsing impact.